Integration Of Artificial Intelligence In Sensory Marketing And Its Influence On The Emotions Of Generation Z Consumers In Coffee Cafes - Totok Haryanto; Meydy Fauziridwan; Lahan Adi Purwanto (Green Publisher Indonesia, 2024)
This study aims to measure the influence of artificial intelligence (AI)-based sensory marketing on PAD emotions (Pleasure, Arousal, Dominance) and consumer behavioral intention in the context of cafes. The study used an experimental method by dividing respondents into two groups: one group received AI-based sensory marketing interventions, while the other group experienced conventional sensory marketing without AI. Data was collected using a questionnaire that measured PAD emotions and behavioral intentions after interaction with the café environment. Statistical analyses were conducted using the Independent Sample t-test, ANOVA, Cohen's d, and Moderation Analysis to evaluate significant differences between the two groups and to understand the moderation effect of brand experience on outcomes. The results showed that AI intervention did not have a significant effect on consumer emotions or behavioral intention, with a p-value of >0.05 for all variables measured. The effect measure (Cohen's d) also indicated that the differences between the groups were very small and practically insignificant. Additionally, brand experience was not found to be a moderator that reinforces the relationship between AI interventions and emotional or behavioral variables